Consume, Contribute, and Create: Succeeding as a Learner and Educator in the Digital Era - Gurleen Kaur; Daniel Ambinder; Amit Goyal (Methodist DeBakey Cardiovascular Journal)
From medical student to professorship, the practice of medicine requires lifelong learning. The unforgivingly rapid expansion of medical literature often renders traditional educational resources quickly outdated if not altogether obsolete. Conversely, increasingly popular digital platforms are easily accessible and quickly updated, offering vital adjuncts to traditional resources for the modern student. Further, platforms such as podcasts and social media may be particularly well suited for adult learners who tend to be problem centered, self-directed, internally motivated, and time constrained. Social media empowers all participants, thereby blurring the boundaries between learners and educators. Here we review novel digital educational platforms, discussing both potential benefits and pitfalls, and then provide a three-pillared approach—consume, contribute, and create—to help the modern medical professional harness the potential of both traditional and novel resources to succeed as both a learner and educator.